2001
DOI: 10.1073/pnas.091095898
|View full text |Cite
|
Sign up to set email alerts
|

Sequence conservation at human and mouse orthologous common fragile regions, FRA3B / FHIT and Fra14A2 / Fhit

Abstract: It has been suggested that delayed DNA replication underlies fragility at common human fragile sites, but specific sequences responsible for expression of these inducible fragile sites have not been identified. One approach to identify such cis-acting sequences within the large nonexonic regions of fragile sites would be to identify conserved functional elements within orthologous fragile sites by interspecies sequence comparison. This study describes a comparison of orthologous fragile regions, the human FRA3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 35 publications
(49 reference statements)
0
52
0
1
Order By: Relevance
“…Both FRA3B and FRA16D represent fragile regions in the mouse, Fra14A2 and Fra8E1, respectively (Shiraishi et al, 2001;Krummel et al, 2002). Additionally, the mouse orthologs of FHIT and WWOX (Fhit and Wox1) also appear to have been conserved together through evolution (Shiraishi et al, 2001;Krummel et al, 2002). The FRAXB region is distinct from the other three highly active CFS regions, as instability within this CFS region extends for only 500 kb (Arlt et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both FRA3B and FRA16D represent fragile regions in the mouse, Fra14A2 and Fra8E1, respectively (Shiraishi et al, 2001;Krummel et al, 2002). Additionally, the mouse orthologs of FHIT and WWOX (Fhit and Wox1) also appear to have been conserved together through evolution (Shiraishi et al, 2001;Krummel et al, 2002). The FRAXB region is distinct from the other three highly active CFS regions, as instability within this CFS region extends for only 500 kb (Arlt et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…FRA3B and FRA16D also appear to be highly conserved between humans and mice. Both FRA3B and FRA16D represent fragile regions in the mouse, Fra14A2 and Fra8E1, respectively (Shiraishi et al, 2001;Krummel et al, 2002). Additionally, the mouse orthologs of FHIT and WWOX (Fhit and Wox1) also appear to have been conserved together through evolution (Shiraishi et al, 2001;Krummel et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, significant variation in the level of sequence conservation between human and mouse from locus to locus has been reported in several studies of long DNA sequences of single loci (Hardison et al 1991(Hardison et al , 1997Koop 1995;DeBry and Seldin 1996;Gött-gens et al 2001;Shiraishi et al 2001;Wilson et al 2001) and in comparative studies of gene sequences in these and other mammals (Wolfe et al 1989;Bernardi 1993Bernardi , 1995Casane et al 1997;Matassi et al 1999;Williams and Hurst 2000;Lercher et al 2001;Castresana 2002a,b), albeit with some dissenting analysis (Williams and Hurst 2000;Kumar and Subramanian 2002). With ∼700 4D sites/Mb and 50,000 AR sites/Mb genome-wide, we were able to do a much larger scale study of regional variation in rates of substitution, and found correlated fluctuations in regional substitution rates for both types of sites.…”
Section: Large-scale Regional Variation and Covariation In Rates Of Smentioning
confidence: 99%
“…The chromosomal fragile sites varied depending on breed and age, but chromosome 20, which contains the canine FHIT gene locus, was not identified as a fragile site [20]. However, the FRA3B/Fra14A2 loci are conserved in ATrich sequences with numerous short and long repeats throughout the region [9,18]. The intronic regions of the canine FHIT gene also have AT-rich short repeat sequences (data not shown).…”
mentioning
confidence: 99%
“…Moreover, its amino acid sequence was extremely similar to those of the other species. In the human and mouse, the FHIT gene is located in the unstable fragile regions of the genomes, FRA3B and Fra14A2, respectively [18,19]. A previous study reported the canine folate/thymidine depleted and aphidicolin-inducible fragile site using PBMCs from the Boxer and Doberman Pinscher breeds.…”
mentioning
confidence: 99%